Les Représentations savantes des usagers dans la collection « L’Architecture rurale française » : l’exemple du Dauphiné - Frédéric Firreri (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This article takes a retrospective look at the notion of the ’user’ in the context of the collection of works entitled “L’Architecture rurale française”, directed by Jean Cuisenier, from 1977 to 2001. By revealing the underlying narrative structures of the scientific analysis carried out by Henri Raulin on the first volume published, Dauphiné, this article attempts both to shed light on the processes that constructed a learned representation of popular architecture, and to highlight the disciplinary and institutional mechanisms that enabled the emergence of an anthropological theory of architecture.